Comparison of Compressive Strength of Zirconia Reinforced Glass Ionomer Cement and Amalgam - Chawantanphiphat, Yodsawadee; Putthipat, Nongwipa (Journal of The Department of Medical Services, 2021)
Background: Currently, the trend of amalgam usage is decreasing, due to the development of adhesive systems and toxicity from mercury, and also the development of tooth-colored restorations materials. Glass ionomer cement is one of the ideal tooth-colored restorative material and has fluoride release to prevent dental caries but the disadvantage is the low compressive strength. Therefore, it has been developed by adding zirconia in glass ionomer cement to increase a high compressive strength.Objective: The aims of this research were to evaluate and compare the compressive strength of restorative material zirconia reinforced glass ionomer cement: Zirconomer Improved, amalgam: Tytin FC®, and conventional glass ionomer cement: GC Gold Label 9 Extra.Method: The 30 cylindrical specimens were fabricated by 4 mm in diameter and 6 mm in height then grouped into six study groups (n=5): group I (Zirconomer Improved at 1 hour), group II (Zirconomer Improved at 24 hours), group III (Tytin FC® at 1 hour), group IV (Tytin FC® at 24 hours), group V (GC Gold Label 9 Extra at 1 hour), group VI (GC Gold Label 9 Extra at 24 hours) for testing the compressive strength. The specimens were tested in a universal testing machine (Instron 5566) at a crosshead speed of 0.5 mm/min for compressive strength until failure occurred. Data analysis and statistical differences were ascertained using one - way ANOVA with Tukey post-hoc test (p<0.05).Result: In 1 hour period, the compressive strength was not different between zirconia reinforced glass ionomer cement and amalgam and was higher than that of conventional glass ionomer cement with statistical significance at the level of 0.05. In the 24 hour period, the compressive strength tests showed a significant difference in 3 groups, the highest compressive strength was exhibited by amalgam followed by zirconia reinforced glass ionomer cement and conventional glass ionomer cement respectively.Conclusion: The addition of zirconia increases the strength of glass ionomer cement significantly compared to the conventional glass ionomer cement and equivalent to amalgam at 1 hour but weaker than amalgam at 24 hours.